2021
DOI: 10.5334/cie.32
|View full text |Cite
|
Sign up to set email alerts
|

Sense of School Belonging and Paediatric Illness: A Scoping Review

Abstract: The experience of hospitalization leads children to move away from their everyday life, such as school attendance. Participating in school activities and relating with classmates are important experiences in children's development and promote a general sense of school belonging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 65 publications
1
1
0
2
Order By: Relevance
“…Resonant with existing studies, connectedness and well‐being were important in the school lives of our participants (Forrest et al, 2013; Knight et al, 2018; Kosola et al, 2018; Lum et al, 2019; Maslow et al, 2012; Pini et al, 2012, 2016; Pini, Hugh‐Jones, et al, 2019; Tomberli & Ciucci, 2021). Regardless of the specific need in question, an underlying factor toward positive connection to school was feeling that school staff recognized the young person's needs, made reasonable and sensitive adjustments, and demonstrated a desire to include them in school activities.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Resonant with existing studies, connectedness and well‐being were important in the school lives of our participants (Forrest et al, 2013; Knight et al, 2018; Kosola et al, 2018; Lum et al, 2019; Maslow et al, 2012; Pini et al, 2012, 2016; Pini, Hugh‐Jones, et al, 2019; Tomberli & Ciucci, 2021). Regardless of the specific need in question, an underlying factor toward positive connection to school was feeling that school staff recognized the young person's needs, made reasonable and sensitive adjustments, and demonstrated a desire to include them in school activities.…”
Section: Discussionsupporting
confidence: 70%
“…Research into childhood epilepsy, diabetes and asthma all showed relative deficits in educational attendance or attainment (Flemming, Fitton, Steiner, McLay, Clark, King, Lindsay, et al, 2019; Flemming, 2019a, 2019b). These differences have been attributed to functional status (Forrest et al, 2013), severity of condition (Austin et al, 1998), frequency of health appointments (Eloi et al, 2019), sense of belonging in school (Tomberli & Ciucci, 2021), parent‐perceived health‐related quality of life (Emerson et al, 2016), and in‐class challenges of pain, memory, and concentration (Moorthy et al, 2010). However, a 2023 review found limited evidence that school absence is a mediating factor in the attainment of young people with long‐term health conditions (Jay et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Il ritorno a scuola dopo il ricovero può essere emotivamente e socialmente difficile: spesso i bambini con condizioni mediche perdono il contatto con i compagni di classe, isolandosi e vivendo ansia, depressione e stress; per prevenire queste difficoltà è fondamentale favorire più alti livelli di sense of school belonging (SoSB) nello studente con patologia, affinchè questo si senta ricordato e pensato dai compagni (Tomberli e Ciucci 2021;.…”
Section: Introductionunclassified
“…Given the above challenges, focusing on their sense of belonging is key to supporting children with chronic medical conditions. This focus is achieved by empowering them to interact socially and keep up with their peers ( Hung & Chen, 2008 ; Tomberli & Ciucci, 2021 ). Based on these premises, the Italian Ministry of Work and Social Policies established a special fund in 2017 to support children with oncology diseases and their families ( Law No.…”
mentioning
confidence: 99%